2015
DOI: 10.1159/000430919
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a β-Hydroxyphosphonate Analogue of <smlcap>L</smlcap>-Carnitine on Insulin-Sensitive and Insulin-Resistant 3T3-L1 Adipocytes

Abstract: This study investigated the effect of a β-​hydroxyphosphonate analog of L-carnitine (L-CA) (CAS number: 1220955-​20-3, Component: 1221068-91-2, C12H29NO4PI), (3-Hexanaminium, 1-(dimethoxyphosphinyl)-2-hydroxy-N,N,N,5-​tetramethy-iodide (1:1), (2R, 3S)) on parameters related with type-2 diabetes in an in vitro model. Nontoxic concentrations of L-CA were assayed and compared to commercial L-carnitine effects. L-CA did not affect adipogenesis in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In contrast, lower concentrations did not affect cell viability when compared with the control (zero), without polyphenolic extracts (Figure 1). The maximum toxic concentration of polyphenolic extracts from SCG that sustains 80% of cell viability was calculated using linear regression, (y = −39.564x + 323.2, R 2 = 0.9306) [18,19], and the result was 467.31 µg/mL. These data show that polyphenolic extracts from SCG could be used without cytotoxic effects at concentrations under 467.31 µg/mL.…”
Section: Phenolic Compounds and Antioxidant Capacity Of Polyphenolic Extracts From Scgmentioning
confidence: 82%
“…In contrast, lower concentrations did not affect cell viability when compared with the control (zero), without polyphenolic extracts (Figure 1). The maximum toxic concentration of polyphenolic extracts from SCG that sustains 80% of cell viability was calculated using linear regression, (y = −39.564x + 323.2, R 2 = 0.9306) [18,19], and the result was 467.31 µg/mL. These data show that polyphenolic extracts from SCG could be used without cytotoxic effects at concentrations under 467.31 µg/mL.…”
Section: Phenolic Compounds and Antioxidant Capacity Of Polyphenolic Extracts From Scgmentioning
confidence: 82%
“…1 LC 50 values and LC 20 values were obtained from linear regression analysis. 29 The LC 20 values (referred to as the 'working concentration') were calculated in addition to the LC 50 values, to help inform the working concentrations to be used for the next set of experiments, in which the effects and molecular mechanisms of glyphosate on brain and heart cells of marine fish will be further investigated. The toxicity assays were performed in quadruplicate, and the figures represent the mean value ± SD of four experiments carried out independently.…”
Section: Discussionmentioning
confidence: 99%
“…The LC 50 for brainderived cells was calculated to be 47.3 μg/ml, by using the linear regression equation (y = À34.832x + 113.23; R 2 = 0.9628), and for heart-derived cells it was 49.7 μg/ml (y = À41.361x + 112.12; R 2 = 0.9779). 1,29 The results showed that the heart-derived cells were slightly more sensitive to glyphosate than the brain-derived cells. The working concentration (i.e.…”
Section: Assessment Of Cytotoxicity By Direct Viable Cell Countmentioning
confidence: 97%